1986
DOI: 10.1111/j.1476-5381.1986.tb10208.x
|View full text |Cite
|
Sign up to set email alerts
|

Binding of a radioiodinated 13‐azapinane thromboxane antagonist to platelets: correlation with antiaggregatory activity in different species

Abstract: Binding of a 125I‐labelled derivative of the 13‐azapinane thromboxane antagonist (ONO‐11120), [125I]‐9,11‐dimethylmethano‐11,12‐methano‐16‐(3‐iodo‐4‐hydroxyphenyl)‐13,14‐dihydro‐13‐aza‐15‐β‐ω‐tetranor‐thromboxane A2 ([125I]‐PTA‐OH), to washed platelets of human, dog and rabbit was studied. Results were compared with the in vitro inhibitory potency of ONO‐11120 on platelet aggregation induced by arachidonate and a thromboxane agonist, 9,11‐epithio‐11,12‐methanothromboxane A2 (STA2). [125I]‐PTA‐OH bound to washe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(28 citation statements)
references
References 26 publications
3
25
0
Order By: Relevance
“…STA2 is a highly potent agonist of TXA2 receptors in smooth muscle; it contracted the canine and human saphenous veins with EC50 values of 0·2-0·4 nÒ (Mais et al 1985) and the canine cerebral, coronary, renal and mesenteric arteries with EC50 values of 0·9-1·1 nÒ (Toda, Nakajima, Okamura & Miyazaki, 1986). In contrast, a higher concentration of STA2 was required to produce platelet aggregation; the EC50 values for human (Mais et al 1985;Narumiya, Okuma & Ushikubi, 1986) and rabbit (Narumiya et al 1986) plateletrich plasma were 1·1-1·8 ìÒ and 8·2 ìÒ, respectively. In the present study, STA2 acted as an intermediary potent agonist, causing Cl¦ secretion in the rat colon with an EC50 value of more than 30 nÒ (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…STA2 is a highly potent agonist of TXA2 receptors in smooth muscle; it contracted the canine and human saphenous veins with EC50 values of 0·2-0·4 nÒ (Mais et al 1985) and the canine cerebral, coronary, renal and mesenteric arteries with EC50 values of 0·9-1·1 nÒ (Toda, Nakajima, Okamura & Miyazaki, 1986). In contrast, a higher concentration of STA2 was required to produce platelet aggregation; the EC50 values for human (Mais et al 1985;Narumiya, Okuma & Ushikubi, 1986) and rabbit (Narumiya et al 1986) plateletrich plasma were 1·1-1·8 ìÒ and 8·2 ìÒ, respectively. In the present study, STA2 acted as an intermediary potent agonist, causing Cl¦ secretion in the rat colon with an EC50 value of more than 30 nÒ (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Its aggregatory potency appears to be lower: EC50 = 0.4flM (Katsura et al, 1983) and 1.1UM (Mais et al, 1985) for human PRP, 0.68juM (Mais et al, 1985) for dog PRP and 8jM for rabbit PRP (Narumiya et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…In a preliminary report Anderson & MacIntyre (1982) also showed that EP 045 and several other TP-receptor antagonists were less potent as inhibitors of U-46619-induced aggregation in rabbit platelet-rich plasma (PRP) compared with human PRP. More extensive studies (Narumiya et al, 1986) have shown that the TP antagonist, ONO 11120 (Katsura et al, 1983) (Figure 1), is a less effective inhibitor of aggregation induced by STA2 (a stable TXA2 analogue, Figure 1) in rabbit PRP than in human PRP. In addition, radiolabelled I-PTA-OH, a close relative of ONO 11120, was found to bind with high affinity to TP-receptors on human and dog washed platelets but not rabbit washed platelets.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed studies of the human platelet TXA2/PGH2 receptor have also been performed with ['25I]PTA-OH, a stable radioiodinated TXA2 antagonist. Two different groups have re-ported that [125I]PTA-OH binds to a single site with a capacity of -2,000 sites per platelet (9,10). Though [1251]PTA-OH has a higher specific activity and greater affinity for the receptor than does [3H]U46619, its properties as an antagonist may make it less than ideal for discriminating between different TXA2/PGH2 agonist binding sites (11)(12)(13).…”
mentioning
confidence: 99%